Exploring the Values of the Prophet Muhammad’s Hijrah through a Deep Learning Approach in Islamic Education at Primary School - Tumin, Tumin; Septariani, Sella Fadia (Tafkir: Interdisciplinary Journal of Islamic Education, 2026)
This research examines deep learning approach in the construction of teaching Hijrah of Prophet Muhammad SAW in an elementary Islamic school. This is the research objectives were to explore how reflective, contextual and experiential approaches in the teaching of Islamic religious education (IRE) can internalize moral and spiritual values in young children. This was basic qualitative research with interviews of teachers and students, observations in the classroom, and analysis of documents which was conducted at SDIT Jabal NUR Yogyakarta. The results indicated that deep learning induces emotional involvement in students, increases reflective ability and helps transform behavior through technology integration, storytelling and value activities. Role play, multimedia support and Canva-based reflection activities were used by teachers to facilitate the communication of students’ ideas. Nonetheless, issues such as the restriction of instructional time and lack of affective assessment models and training were revealed. The study finds that the use of deep learning in IRE provides meaningful learning experiences and fosters a cohesive approach to the development of Islamic character during primary education. It also suggests flexibility of the curriculum, reflection with faculty guidance and institutional support to enhance effectiveness of the model.